2006
DOI: 10.1038/modpathol.3800670
|View full text |Cite
|
Sign up to set email alerts
|

Divergent pathway of intestinal metaplasia and cystitis glandularis of the urinary bladder

Abstract: Intestinal metaplasia has been proposed to be a precursor lesion of adenocarcinoma in the urinary bladder. CDX2 is a transcription factor that is encoded by a homeotype gene that plays an essential role in the differentiation and proliferation of intestinal epithelial cells. Hepatocyte-specific antigen (Hep) has also been shown to be a useful marker of intestinal metaplasia. Tissues from 46 patients, including 22 cases of intestinal metaplasia of the urinary bladder, 11 cases of typical cystitis glandularis, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
0
10

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 40 publications
3
51
0
10
Order By: Relevance
“…Previous studies have suggested a close histogenetic and pathogenetic relationship of primary adenocarcinoma of the urinary bladder and colorectal adenocarcinoma. [22][23][24][25][26] Our finding that cadherin-17 and GATA3 expression are very similar in these two tumor types supports this relationship (Table 2). However, positive nuclear and cytoplasmic immunostaining for b-catenin was evident in 95% of (21/ 22) primary and 92% of (23/25) secondary colorectal adenocarcinoma, in contrast to positive membranous and cytoplasmic staining for b-catenin in 92% of (23/25) primary adenocarcinomas of the urinary bladder and 100% of (11/11) urothelial carcinomas with glandular differentiation (Po0.001).…”
Section: Discussionsupporting
confidence: 74%
“…Previous studies have suggested a close histogenetic and pathogenetic relationship of primary adenocarcinoma of the urinary bladder and colorectal adenocarcinoma. [22][23][24][25][26] Our finding that cadherin-17 and GATA3 expression are very similar in these two tumor types supports this relationship (Table 2). However, positive nuclear and cytoplasmic immunostaining for b-catenin was evident in 95% of (21/ 22) primary and 92% of (23/25) secondary colorectal adenocarcinoma, in contrast to positive membranous and cytoplasmic staining for b-catenin in 92% of (23/25) primary adenocarcinomas of the urinary bladder and 100% of (11/11) urothelial carcinomas with glandular differentiation (Po0.001).…”
Section: Discussionsupporting
confidence: 74%
“…Tissues from 34 patients with the diagnosis of intestinal metaplasia of the urinary bladder from 1989 to 2005 were obtained from the Surgical Pathology archives of the participating institutions. All cases were reviewed and diagnosed according to wellaccepted criteria (5,19). The diagnosis of cystitis glandularis was reserved for luminal structures within the lamina propria with peripheral transitional cells and an innermost lining of columnar or cuboidal cells.…”
Section: Methodsmentioning
confidence: 99%
“…The addition of mucin-secreting goblet cells in the lining epithelium has been called cystitis glandularis of the intestinal type (4). Sung et al (5) showed that glandular lesions that include a component of goblet cells within the lining epithelium exhibit an immunoprofile distinctly different from that of lesions that lack goblet cells and suggested that the former be referred to simply as intestinal metaplasia.…”
mentioning
confidence: 99%
“…There are still discordant data on the value of GM as a precancerous lesion. Recent data confirm that intestinal metaplasia and cystitis glandularis involve divergent pathways (6). Telomere shortening and analysis of chromosomal abnormalities support the hypothesis of intestinal metaplasia as a precursor lesion and could be a marker in the development of adenocarcinoma of the urinary bladder (7).…”
Section: Glandular Metaplasia (Gm)mentioning
confidence: 52%